English Teachers’ Challenges in Designing Teaching Module for the Merdeka Curriculum - Sitti Fatimah Yusuf; Chairil Anwar Korompot; Nur Aeni (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This study aims to identify what are the challenges faced by English teachers in designing teaching module in the Merdeka Curriculum. The population of this study is English teachers who teach in grades 7 and 8 at SMP Negeri 1 Takalar. This study involved 3 participants who were determined through purposive sampling. The instruments used in this study were documents and interviews. The challenges faced by English teachers in designing teaching modules for the Merdeka Curriculum include finding methods that match students' conditions and characteristics, dealing with poor internet connections, meeting students' learning needs, considering students' backgrounds and levels of understanding, addressing very basic English proficiency, choosing easily understood words, maintaining student grades, creating various forms of assessments, organizing assessment timing, and providing contextualized teaching. Keywords: Challenges, Teaching Module, Merdeka Curriculum.